Opinie publiczne, pogłoski i zachowania społeczne na Śląsku Opolskim w latach 1945-1947 w świetle sprawozdań i serwisów poufnych Ministerstwa Ziem Odzyskanych i Ministerstwa Informacji i Propagandy = Public opinions, rumours and social behaviour in Opolian Silesia from 1945-1947 in the light of reports and confidential services of the Ministry of Regained Territories and the Ministry of Information and Propaganda - Świder, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It was Machiavelli who assumed that there was no such an authoritative government which could allow itself not to take public opinion in to consideration. Also communist authorities who gained power over territories excluded from Poland in 1945, were interested in public opinion. Information about gossips and feeling among inhabitants of Opolian Silesia was gathered in special reports for the needs of central institutions. Both inhabitants who had just arrived in these territories: repatriates and settlers and indigenous people were under observation.
Keywords: Śląsk Opolski; Ziemie Zachodnie i Północne; zachowania społeczne; historia; po 1944 r.